Level of cultural sensitivity and its influence on teachers’ performance - Baron, Jomarie V. (Journal of Social, Humanity, and Education, 2023)
Purpose: The primary goal of this study was to analyze the level of cultural sensitivity and its impact on the performance of secondary school teachers in Buayan District, Division of General Santos City. This study attempted to identify correlations between cultural sensitivity and secondary teacher performance. Research methodology: The research design of this study was descriptive-correlative. Since the design is descriptive, it provides a full discussion and explanation of teachers' cultural sensitivity and its impact on their performance. Furthermore, the study's methodology aimed to identify significant correlations between the variables under investigation. The mean and Pearson product-moment correlations were the statistical measures employed to evaluate the hypotheses. Results: The findings revealed a significant, moderate, and direct relationship between cultural sensitivity and teacher performance. Consequently, strengthening teachers' cultural sensitivity may improve their performance. Limitations: This study was limited to three (3) Buayan District Public Secondary Schools. The variables under consideration were narrowed down because cultural sensitivity is only concerned with the value system, belief system, decision making, and cross-cultural communication. On the other hand, teachers’ performance variables focused only on the teaching and learning processes, student outcomes, and community involvement. Contribution: The findings of this study provide information on teachers' levels of cultural sensitivity as a foundation for improving their performance and developing a curriculum for teaching in various cultures. Novelty: This study's originality focuses on its factors, which integrate cultural sensitivity and teachers’ performance. This research aids in determining the impact of teachers' cultural sensitivity on their performance.